The Russian Textbook: Problems in Teaching Russian to Migrant Workers and Their Families: An Overview of Teaching Materials - Sofiya Russkikh; Polina Kovalyova (The February Journal)
This article analyzes extant Russian-as-a-foreign-language (RAF) textbooks aimed at migrant workers. These textbooks do not fully meet the needs of migrant workers and their families: the majority of the RAF materials are written for university students, assuming that the students have the language skills needed for professional communication, while general-type textbooks aimed at mastering a practical course of Russian tend to be addressed to Westerners. The authors analyze the books in the broader context of migration in today’s Russia from anthropological, pedagogical, and linguistic perspectives.